BAGAIMANA MENGURANGI BIAS KEMURAHAN HATI DALAM PENILAIAN KINERJA SUBJEKTIF? SEBUAH PENDEKATAN EKSPERIMEN - Handojono, Monika; Sholihin, Mahfud (UI Scholars Hub, 2014)
The literature shows that leniency has negative impact on employee performance and firm productivity. However, there has been limited empirical research of how to mitigate the bias. This study examines if leniency is mitigateable by availability of subjective evaluation criteria and group rater. Using experimental method with sixty-nine undergraduate students as subjects, we find that process within group is effective to reduce individual subjective rating, even when there was no subjective criteria. However, we find group rating does not have effect on rating accuracy. Additionally, consistent with general assumption of leniency, we find that inflated rating is affected by altruistic traits of raters. With the inherent limitations associated with experimental method, our finding suggests that, in order to have subjective rating accurately, firm should promote sound rating process by defining more relevant criteria to complement the evaluation process.